Bio efficacy of mycoacaricides against two spotted spider mite, Tetranychus urticae - K V, Raghavendra; C, Chinniah; R, Gowthami (Indian Journal of Plant Protection, 2020)
An investigation was carried out in in-vitro condition to screen locally available commercial formulations of five mycoacaricides with different spore concentrations against Tetranychus urticae Koch based on per cent mortality of mites and per cent reduction in egg laying by mites. The present study revealed that the standard check (propargite 57 EC @ 2.00ml/l) was significantly superior than the mycoacaricides evaluated in terms of mortality of adults (86.38 per cent) and reduction of eggs (76.37 per cent) respectively. But, among the mycoacaricides evaluated, Beauveria bassiana @ 1x1010 CFU/ml, B. bassiana @ 1x108 CFU/ml, Lecanicillium lecanii @ 1x1010 CFU/ml and L. lecanii @ 1x108 CFU/ml recorded the maximum per cent mortality of mites (78.68, 77.76, 77.04 and 76.35 per cent) and the maximum per cent reduction of eggs (69.97, 69.15, 68.52 and 68.14 per cent) respectively, which were statistically on par in their efficacy. From the present study it is apparent that B. bassiana @ 1x108 CFU/ml and L. lecanii @ 1x108 CFU/ml were found to be the promising candidates which can be a better options as substitutes to synthetic chemical acaricides for the management of T. urticae Koch infesting most of the agricultural and horticultural crops.